Pengaruh Kemampuan dan Motivasi terhadap Prestasi Kerja Pegawai pada Unit Perawatan Pesawat Udara dalam Mendukung Praktik Latihan Terbang di STPI Curug - Driyono, Bambang (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
Skill Influence and Motivation Against Employee Job Performance in the Aircraft Maintenance unit in the Supporting Flying Practices at STPI Curug. This research was done in order: (1) to verify and analyze the capability of impact towards work performance ; (2) to verify and analyze the motivation impact towards work performance ; (3) to verify and analyze the impact towards capability and motivation simultaneously (at the same time) towards work performance.This research used primary data through 33 surveys of employees as a sample from the whole employees population as such 33 respondents. The research indicates that: (1) validity test could be stated as valid on every item questioned because it is obtained r counts > table r. On the other hand, from the reliability test of every item questioned could be stated reliable ; (2) significance value for the impact of X1 towards Y is 0.024< 0.05 and value t_counts 2.386> 2.042, so it can be summed that H1 could be accepted which means there is an influence capability of variable X1 towards work performance of variable Y ; (3) significance value for the impact of X2 towards Y is 0.000 < 0.05 and value t_counts 5.367 > 2.042, so it can be summed that H2 could be accepted, which means there is an influence capability of X2 towards work performance of variable Y ; (4) significance value for the impact of X1 and X2 towards Y is 0.000 < 0.05 andF_counts value in the amount of 24.774 > 3.30, so it can be summed that H3 could be accepted, which means there is an influence capability of variable (X1) and motivation of variable (X2) simultaneously towards work performance (Y); (5) the value R_square of 0.623, which means is that the influence between capability as variable (X1) and motivation as variable (X2) simultaneously towards work performance variable (Y) is 62.3%, then it can be obtained the multiple regression linier with equation : Y = -2.836 + 0.344X1 + 0.692X2.